UNDERSTANDING VYGOTSKY’S ZONE OF PROXIMAL DEVELOPMENT FOR LEARNING - Rentauli Mariah Silalahi (Universitas Pelita Harapan, 2019)
Vygotsky is the father of the Zone of Proximal Development (ZPD) theory who claims that a leaner can do what he can almost do alone with the presence of assistance. This literature study aims at investigating what factors need to be present for developing someone’s potential. From the literature study, it was found that there are six factors that need to be present, including assistance, mediation, cooperation, imitation, target and crises. With the presence of assistance from the more capable other and keeping attention to the six important factors, a learner will be able to do what he/she can almost do alone.BAHASA INDONESIA ABSTRAK: Vygotsky adalah penemu konsep Zona Perkembangan Proksimal yang menyatakan bahwa seseorang yang belajar akan mampu melakukan apa yang hampir dapat dilakukannya secara mandiri dengan tersedianya bantuan. Studi kepustakaan ini bertujuan untuk meneliti unsur apa saja yang penting untuk membantu perkembangan potensi seorang pelajar. Dari studi kepustakaan ditemukan bahwa ada enam unsur yang penting yakni bantuan, mediasi, kerjasama, kemampuan untuk meniru, sasaran dan masa sulit atau keluar dari zona nyaman. Dengan adanya bantuan dari orang yang lebih mampu dan kehadiran dari enam unsur tersebut, seorang pelajar akan mampu melakukan apa yang hampir dapat dilakukannya sendiri.